The Science and Technology of 3D Printing - Mukherjee, Tuhin (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Three-dimensional printing, or additive manufacturing, is an emerging manufacturing process. Research and development are being performed worldwide to provide a better understanding of the science and technology of 3D printing to make high-quality parts in a cost-effective and time-efficient manner. This book includes contemporary, unique, and impactful research on 3D printing from leading organizations worldwide.